HETEROGENEOUS MARKETING APPROACHES IN SOCIAL MEDIA MARKETING; AN EXAMINATION OF CUSTOMER VALUE - Saini, Mankeshva; TP, Krishna Kumar; Saravanan K; J., Vinothalakshmi; Barman, Suman Roy; Roop Raj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study examined the role of heterogeneous marketing approaches in social media marketing (SMM) and their impact on customer value. As businesses increasingly leverage social media platforms to engage diverse audiences, a one-size-fits-all approach no longer suffices. Heterogeneous marketing strategies, which adapt messaging, content, and interaction based on customer segments, have proven more effective in delivering personalized experiences. The article explored how such approaches influence customer value dimensions, including perceived value, loyalty, and purchase intention. Using case studies and empirical data, the study investigates the effectiveness of different social media marketing tactics across various demographics, helping marketers refine their strategies for optimal results. 150 respondents were selected by choosing convenient random sampling technique. The consumers agreed on the factor influencing Heterogeneous Marketing Approaches in Social Media Marketing in the study region. Personalization, enhanced engagement, optimized ad spend, improved customer experience, and valuable insights all contribute to the success of these strategies. The authors recommend that brands leverage insights from social media analytics to fine-tune their strategies for each platform, thereby enhancing their ability to create meaningful interactions and drive customer value. By addressing the unique characteristics of various customer groups, brands can create more impactful and meaningful interactions, ultimately driving greater satisfaction, loyalty, and business success.